The Impact of Aging on the Lung Alveolar Environment, Predetermining Susceptibility to Respiratory Infections - Torrelles, Jordi B.; Restrepo, Blanca I.; Bai, Yidong; Ross, Corinna; Schlesinger, Larry S.; Turner, Joanne (Frontiers in Aging, 2022)
Respiratory infections are one of the top causes of death in the elderly population, displaying susceptibility factors with increasing age that are potentially amenable to interventions. We posit that with increasing age there are predictable tissue-specific changes that prevent the immune system from working effectively in the lung. This mini-review highlights recent evidence for altered local tissue environment factors as we age focusing on increased tissue oxidative stress with associated immune cell changes, likely driven by the byproducts of age-associated inflammatory disease. Potential intervention points are presented.